The Employment of Foundational Indicators in the Interpretation of Inheritance Verses - Mikhlf , Noor AbdulKarim; Juma , Suhaib Abbas Odeh (Journal of Ecohumanism, 2024)
This study, titled "Utilizing Fundamental Indications in Interpreting Verses of Inheritance," aims to show the significance of the science of indications in fundamental research and interpretive methodology, and how to employ indications in understanding legal texts. It reviewed the verses of rulings related to the science of shares as a starting point to apply and activate the theoretical aspect, providing a fertile ground to illustrate the methodology of interpreters and jurists in deriving legal rulings and reading the text with its words, implications, and meanings. The study concluded that the first step in understanding meanings is to know the indication, as it directs the texts toward the purpose for which they were revealed. These texts were meant to keep pace with the times and meet people's needs in light of emerging developments. Since these meanings are sometimes derived from the apparent aspects of explicit texts and sometimes from their hidden aspects, which the mind can only grasp through deeper contemplation and reflection, it is essential for anyone who issues judgments and fatwas based on the texts of the two revelations to be knowledgeable about how to uncover meanings and their intentions from words, while considering the methods of derivation that lead to clarifying the legal ruling.